Déficit de atención y bajas calificaciones en niños de la Unidad Educativa Mons. Alberto Zambrano Palacios – Olmedo - Tapia Tapia, Karina del Cisne (2023)
Attention Deficit Disorder with or without Hyperactivity is the childhood’s disorders that generates difficulties the last a lifetime, school causing, family, and social problems and is associated with learning disorders. According to the DSM-V and ICD-10, clinical manifestations last more than 6 months to be considered ADHD. A prevalence of 5.9 to 7.1% has been reported globally between the ages of 8 to 14 years, where it is considered that the greater the Difficulty of Attention, the quality of the child’s life is more affected. Due to the importance of the problem, this quantitative, correlational, prospective, cross-sectional study had the purpose of characterizing sociodemographically, identifying the presence of Attention Deficit and establishing the relationship between Attention Deficit and low grades in the Mons Educational Unit. Alberto Zambrano Palacios of the Olmedo canton. For which the Conners Test was applied to 65 children, where it was found that 50.77% (n=33) were girls and 49.23% (n=32) were boys. It was evidenced that 33.85% (n=22) of the study group are in seventh grade, regarding Attention Deficit it was obtained that 64.6% (n=42) manifested suspicion of Attention Deficit of which 20 % (n=13) represents seventh grade, finally 35.4% (n=23) present suspicion of attention deficit with low grades, while 30.8% (20) present good grades without suspicion of attention deficit. By relating the two variables using Chi-square, he established that there is a statistically significant association, reaching the conclusion that Attention Deficit does lead to low grades